Reading Literacy Comics: Innovative Learning Media on the Theme of Energy and its Changes - Dewi, Luh Gede Santhika; Jampel, I Nyoman; Wibawa, I Made Citra (International Journal of Elementary Education, 2023)
Teachers' use of learning media in the learning process currently needs to be helping students in learning activities. This research aims to develop Reading Literacy Comic Learning Media on energy and its changes. This type of research is development research using the ADDIE model. The subjects of this study were one learning material expert and one learning media expert. The test subjects were two teachers and 13 third-grade students. Data collection methods use observation, interviews, literature studies, and questionnaires. The questionnaire is used to obtain an expert's assessment. The instrument used in collecting data is a questionnaire sheet. The techniques used for data analysis are descriptive qualitative and quantitative analysis. The result of the research is the assessment given by the content expert, which is 96.91% (very good). The assessment results given by learning media experts were 88.95% very good). The teacher's practicality test result was 93.74%, so the qualification was very practical. The test results from students get a score of 95.32%, so they get very good qualifications. Based on this, it can be concluded that reading literacy comic learning media is very good and suitable for learning.